MURDER HORNETS - Jaycox, Jaclyn, 1983-; Huff, Abby (North Mankato, Minnesota : Pebble, an imprint of Capstone, 2023)
"Murder hornets are big! They are the largest hornet on Earth. Also called Asian giant hornets, these fierce insects will eat bees and wasps. Young readers can get all the facts with easy text and exciting photos"-- Provided by publisher
Includes index
"Pebble explore"--Back cover.
Bibliography : page 31
Ages 5-8 Grades K-1
Keywords: Hornets -- Juvenile literature; Insects -- Juvenile literature